2016
DOI: 10.1111/ases.12282
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repeat hepatectomy after right hepatopancreaticoduodenectomy

Abstract: Although laparoscopic hepatectomy is widely accepted for primary hepatectomy, the clinical value of laparoscopic hepatectomy for repeat hepatectomy is still challenging. We herein describe our experience with laparoscopic repeat hepatectomy after right hepatopancreaticoduodenectomy. A 72-year-old woman who had undergone right hepatopancreaticoduodenectomy for perihilar cholangiocarcinoma 31 months prior was diagnosed with liver metastasis in segment 3. We performed laparoscopic repeat hepatectomy. Because mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Regarding noncomparative studies, the intraoperative outcomes were investigated and are demonstrated in Figure , and shown in Table . Meta‐analysis of single proportions for noncomparative studies has shown estimated sizes of 0.49 for major liver resections (95% CI, 0.24‐0.74/heterogeneity I 2 36.53%, Figure A), 0.18 for overall (95% CI, 0.05‐0.34/heterogeneity I 2 = 0; Figure B) and 0.07 for major morbidities (95% CI, 0.03‐0.17; heterogeneity; likelihood ratio test χ 2 = 0; Figure C) and 0.03 for perioperative mortality (95% CI, 0.01‐0.11/heterogeneity; likelihood ratio test χ 2 = 0; Figure D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding noncomparative studies, the intraoperative outcomes were investigated and are demonstrated in Figure , and shown in Table . Meta‐analysis of single proportions for noncomparative studies has shown estimated sizes of 0.49 for major liver resections (95% CI, 0.24‐0.74/heterogeneity I 2 36.53%, Figure A), 0.18 for overall (95% CI, 0.05‐0.34/heterogeneity I 2 = 0; Figure B) and 0.07 for major morbidities (95% CI, 0.03‐0.17; heterogeneity; likelihood ratio test χ 2 = 0; Figure C) and 0.03 for perioperative mortality (95% CI, 0.01‐0.11/heterogeneity; likelihood ratio test χ 2 = 0; Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…13 | 865 cohort studies) and nine noncomparative studies were included for analysis. 7,[26][27][28][29][30][31][32][33][34][35][36][37] For pCCA analysis, one comparative study (retrospective cohort) and nine noncomparative studies were included. [38][39][40][41][42][43][44][45][46][47][48][49] Two records had data regarding both iCCA and pCCA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation